Microfluidic Passive Flow Regulatory Device with an Integrated Check Valve for Enhanced Flow Control - Xinjie Zhang; Zhenyu Zhang (Micromachines, 2019)
A passive microvalve has appealing advantages in cost-effective and miniaturized microfluidic applications. In this work, we present a passive flow regulatory device for enhanced flow control in a microfluidic environment. The device was integrated with two functional elements, including a flow regulating valve and a flow check valve. Importantly, the flow regulating valve could maintain a stable flow rate over a threshold liquid pressure, and the flow check valve enabled effective liquid on/off control, thus accurate forward flow without any backward leakage was achieved. The flow performance of the flow regulating valve was analyzed through 3D FSI (Fluid-Structure Interaction) simulation, and several key parameters (i.e., fluidic channel height and width, control channel length, and Young’s modulus) were found to influence valve flow rate directly. To examine the flow characteristics of the device, we fabricated a prototype using 3D printing and UV laser cutting technologies, and the flow rates of the prototype under varied test pressures were measured in forward and reverse modes, respectively. Experimental results showed that nearly a constant flow rate of 0.42 ± 0.02 mL s−1 was achieved in the forward mode at an inlet pressure range of 70 kPa to 130 kPa, and liquid flow was totally stopped in the reverse mode at a maximum pressure of 200 kPa. The proposed microfluidic flow regulatory device could be employed for accurate flow control in low-cost and portable Lab-on-a-Chip (LoC) applications.